Case Report: Postoperative ascites: allergic reaction to the drainage tube in a 12-year-old patient - Jiang, Ren-sen; Lao, Jing; Wang, Huan-sheng; Wu, Miao-bing; Wang, Bing; Wang, Jian-yao (Frontiers in Surgery, 2024)
Allergic reaction to the silicone is rare in children and as a result very little experience has been reported on symptom and treatment. We presented a case involving a child who experienced prolonged ascites following a surgery of placing an abdominal drainage tube, characterized by the ongoing drainage of clear, light-yellow fluid at a rate of 250 mL/day through the drainage tube for 36 days. Examination of the ascitic fluid revealed an abnormal elevation in eosinophil proportion, which exhibited positive response to anti-allergic treatment. Subsequent to the removal of the drainage tube, the ascites gradually resolved. In conclusion, we presented here the first and youngest case of allergic ascites associated with drainage tube after surgery of ovarian mucinous cystadenoma, it is imperative not to overlook the possibility of drainage tube allergy in the diagnostic process.